STUDI OPTIMALISASI KOMPOSISI GLISEROL DAN KITOSAN TERHADAP KARAKTERISTIK SIFAT FISIK PLASTIK BIODEGRADABLE DARI LIMBAH NASI AKING DAN TEPUNG TAPIOKA - Nurhidayanti, Nisa; Kusuma Wardani, Indah Yulian; Ilyas, Nur Ilman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 15 No 1 (2021), 2021)
Aking rice is rice waste that is no longer suitable for public consumption, however, the high starch content of aking rice can be used as a raw material for making biodegradable plastics. Good biodegradable plastic made from cassava starch and rice flour, to increase its elasticity and extensibility it is necessary to add chitosan additives and glycerol plasticizers. This study aims to determine the optimum conditions for the composition of glycerol and chitosan for the physical properties of biodegradable plastics made from aking rice and tapioca starch. Biodegradable plastics in this study were made with 3 grams of aking rice flour and 7 grams of tapioka flour with the addition of variations in the composition of chitosan (3 grams, 5 grams, and 7 grams) and the addition of variations in the composition of glycerol (2 ml, 4 ml, 6 ml, and 8 ml). As a result, the highest tensile strength value at 7: 2 composition variation is 41.29 MPa, the highest elongation percentage at 3: 8 composition variation is 135.8%, the highest water resistance at 7: 8 composition variation is -206%, the highest percent water absorption and the fastest biodegradation process at a variation of the composition of 3: 2, namely 1603% and completely degraded on the 4th day. Keywords: aking rice, biodegradable plastic, chitosan, glycerol and tapioca starch.